Preliminary phytochemical screening and antimicrobial activity of Tagbak (Alpinia elegans) leaf and rhizome methanolic extracts and solvent fractions - Barongo, Christine Joy A.
The increasing prevalence of bacterial infections and the side effects of synthetic drugs pose significant challenges in today's society, prompting researchers to exp;lore alternative sources of novel antibiotics, including plant extracts. Alpinia elegans, commonly known as "tagbak," has been utilized as a traditional medicine and has shown antibacterial properties. This study focused on investigating the phytochemicals and antimicrobial properties of A. elegans. The phytochemical screening of the leaf crude methanolic extract and solvent fractions revealed the presence of alkaloids, flavonoids, saponins, phenols, tannins, cardiac glycosides, and terpenoids, while the rhizome crude extract and fractions have alkaloids, flavonoids, saponins, and terpenoids. These findings indicate the leaves' higher abundance of phytochemicals compared to the rhizomes. Antimicrobial susceptibility testing revealed the antimicrobial activities of the leaf extracts. Specifically, the leaf crude extract exhibited activity against S. aureus, with a zone of inhibition (ZOI) of 12.10 + or - 0.12 mm while leaf dichloromethane fraction demonstrated inhibition of 12.94 + or - 0.09 mm against A. niger. The minimum inhibitory concentration (MIC) for both extracts was 150.00 + or - 0.00 mg/mL, higher compared to other Alpinia species. The rhizome extracts and fractions did not show any antimicrobial activity. These findings highlight the potential of A. elegans leaf as a source of antimicrobial compounds.